A multifaceted approach to building capacity for marine/maritime spatial planning based on European experience. (October 2021) - Ansong, J.; Calado, H.; Gilliland, P.M.
Abstract: Over the past decade, marine/maritime spatial planning (MSP) has matured from a concept to a practical approach in advancing sustainable development and management of marine space [1]. However, MSP still remains a relatively novel and complex process which involves various disciplines, procedures and engagement with multiple interests within differing governance arrangements and legal settings at different spatial scales in a dynamic system. MSP, therefore, requires marine planning practitioners and their institutions to be adequately equipped to address all of these and emerging challenges. Europe has invested in capacity building for MSP over the years with the adoption of the MSP Directive [2 ] being the main driver for implementation in some Member States alongside those where MSP had already been initiated. This paper provides an overview of experience, practical challenges, and lessons learnt from capacity building initiatives to do with education and training courses, establishing a national planning body, and cross-border projects, mainly from Europe. The paper broadly considers the skills, training and knowledge required for the MSP process. It stresses the importance of developing capacity at all levels, prioritising resources for capacity building and ensuring effective partnerships between the different actors and institutions. Finally, recommendations, potential next steps and priorities are suggested for furthering MSP capacity building.